Soil physico-chemical properties and baby corn yield under green manure and phosphorus application in acid soil - KAR, IPSITA; RAM, VISHRAM; THAKURIA, D.; BORA, P. K.; BEHERA, B. (Journal of Soil and Water Conservation, 2021)
The present investigation was carried out at College of Post Graduate Studies, Central Agricultural University, Umiam, Meghalaya, India during two successive crop seasons, summer and kharif, 2012 to study the interaction effects of green manure and phosphorus on physical and chemical properties of acid soil and baby corn yield. In summer season, the field experiment consisted of six treatment combination of two in situ green manuring treatments viz., without and with green manuring, and three phosphorus application rates (0, 30, 60 kg P2O5 ha-1) supplied through single super phosphate. In kharif, the baby corn was sown with the common dose of fertilizer. With the addition of green manure, the bulk density reduced and the porosity increased appreciably. It was found that the incorporation of green manure in summer readily enhanced the organic carbon content in soil by 24.3%, while the residual effect of green manure in kharif improved the organic carbon by 17. 6% over plots without green manuring. Direct and residual effect of green manure influenced the available nitrogen by 1.1 and 1.06 times and available phosphorus by 1.17 and 1.47 times in soil. The organic carbon content and available phosphorus increased with the increasing levels of phosphorus with both the direct as well as residual effect. The interaction effect of green manure and inorganic phosphorus positively influenced the availability of nitrogen and phosphorus and also augmented the organic carbon in soil.